Secondary metabolites and antioxidant capacity of the hydroalcoholic extract of the leaves of Minthostachys mollis (muña) - Cano P., Carlos (2020)
The objective of the present investigation was to identify some secondary metabolites in the hydroalcoholic extract of leaves of Minthostachys mollis (muña), and determine its antioxidant capacity. The plant species was collected in the district of Huamanguilla (3276 masl), province of Huanta, Ayacucho. The extract was prepared with dried powdered leaves of Minthostachys mollis (muña), by hydroalcoholic maceration, with which solubility tests were carried out with solvents of different polarity, as well as the phytochemical march, then some secondary metabolites were separated by layer chromatography fine obtaining 12 fractions which were read to the UV-vis spectrophotometer. In the hydroalcoholic extract its antioxidant capacity (DPPH, ABTS) was determined. The chemical structure of 5 flavones and 1 flavanone is proposed by visible UV spectroscopy. Good antioxidant capacity was found using the DPPH and ABTS methods.